MODELS OF POLYGAMY REGULATION AROUND THE WORLD: A COMPARATIVE LEGAL ANALYSIS AND ITS IMPLICATIONS FOR WOMEN’S RIGHTS - Agus Salim; Sukiati Sukiati; Iwan Iwan (Al-Muqaranah : Jurnal Perbandingan Hukum dan Mazhab, 2026)
Polygamy is one of the most controversial issues in Islamic family law, continuously debated from both normative and comparative perspectives. This study aims to analyze the legal regulation of polygamy from a comparative law perspective, covering both Muslim-majority countries and those that have undergone significant family law reform. The method employed is normative legal research using a comparative approach and a conceptual approach. Data sources consist of primary, secondary, and tertiary legal materials analyzed through qualitative-descriptive analysis. The findings indicate three models of polygamy regulation in the Muslim world: first, countries that absolutely prohibit polygamy (such as Tunisia and Turkey); second, countries that permit polygamy under strict conditions through judicial oversight (such as Indonesia and Morocco); and third, countries that permit polygamy with minimal conditions based on classical fiqh (such as Saudi Arabia and Malaysia). These regulatory differences are influenced by historical, political, socio-cultural factors, and local scholarly ijtihad. In conclusion, comparative law demonstrates that there is no single universal model for regulating polygamy in Islam, and each country retains its own authority to interpret and implement Islamic law in accordance with its local context.Keyword: Polygamy; Comparative Law; Islamic Family Law; Law Reform; Marriage.